THE DEVELOPMENT OF INTERACTIVE LEARNING CD IN CHEMISTRY FOR HIGH SCHOOLS BASED ON INTERTEXTUALITY AS A LEARNING MODEL ALTERNATIVE - Anwar, Sjaeful; Sonjaya, Yaya; Wiji, Wiji (Faculty of Mathematics and Science Education, Universitas Pendidikan Indonesia, 2011)
ABSTRACT The study application of intertextuality learning model using the CD learning has been conducted in 3 high schools, SMA A, SMA B, and SMA C, during on May 2010. Selection of these three schools are expected to represent the school with low quality to high quality. During the process of learning trials take place, students can actively follow by providing a good response. From the displays are given, students can grasp the concepts of salt hydrolysis on the material well, although sometimes these views should be given back and forth for three levels of representation can link. In general, students responded well to the implementation of this intertextual learning strategy because it was interested in the learning process is done and easy to understand the concepts provided in a systematic and always connects with concepts already learned. The response of teachers towards the implementation of this intertextual learning model provides a positive outlook, in this case because the learning process undertaken to facilitate teachers to deliver material salt hydrolysis systematically arranged through third-level engagement representations and packaged in a multimedia form so that the concepts presented to received by students in one piece and easy. Application of learning models on material intertextual salt hydrolysis was able to improve the mastery of the concepts in the material. Increasing students' mastery of the concept of material obtained by hydrolysis salt N-gain value calculation, the overall values obtained N-gain of 0.67 which means the implementation of learning strategy on material intertextual hydrolysis of this salt can enhance the mastery of concepts with high criteria. This data also supported students' mental models for dissolution process of various salts. This model was also to increase student motivation in learning. Increased student motivation most high school students owned by C, which in most low pretest value compared other high school.Keyword : intertextuality learning modelABSTRAK Studi aplikasi model pembelajaran intertekstual menggunakan CD pembelajaran telah dilakukan di 3 SMA, yaitu SMA A, SMA B dan SMA C selama bulan Mei 2010. Pemilihan tiga sekolah ini diharapkan dapat mewakili sekolah dengan kualitas rendah sampai kualitas tinggi. Selama proses ujicoba pembelajaran berlangsung, siswa dapat mengikuti secara aktif dengan memberikan respon yang baik. Dari tampilan-tampilan yang diberikan, siswa bisa memahami konsep-konsep pada materi hidrolisis garam dengan baik meskipun terkadang tampilan tersebut harus diberikan secara bolakbalik untuk dapat mempertautkan ketiga level representasi. Secara umum, siswa merespon dengan baik terhadap implementasi strategi pembelajaran intertekstual ini karena merasa tertarik dengan proses pembelajaran yang dilakukan dan memudahkan untuk memahami konsep-konsep yang diberikan secara sistematis dan selalu menghubungkan dengan konsep-konsep yang sudah dipelajari. Tanggapan guru terhadap implementasi strategi pembelajaran intertekstual ini memberikan pandangan yang positif, hal tersebut dikarenakan dengan proses pembelajaran yang dilakukan dapat memudahkan guru untuk menyampaikan materi hidrolisis garam yang disusun secara sistematis melalui pertautan ketiga level representasi dan dikemas dalam bentuk multimedia sehingga konsepkonsep yang disampaikan dapat diterima oleh siswa dengan utuh dan mudah. Aplikasi model pembelajaran intertekstual pada materi hidrolisis garam ternyata mampu meningkatkan penguasaan konsep-konsep pada materi tersebut. Peningkatan penguasaan konsep siswa terhadap materi hidrolisis garam diperoleh berdasarkan perhitungan nilai N-gain, secara keseluruhan diperoleh nilai N-gain sebesar 0,67 yang berarti implementasi strategi pembelajaran intertekstual pada materi hidrolisis garam ini dapat meningkatkan penguasaan konsep dengan kriteria tinggi. Hal ini didukung juga data model mental siswa untuk proses pelarutan berbagai garam. Model ini ternyata juga dapat meningkatkan motivasi siswa dalam pembelajaran. Peningkatan motivasi siswa paling tinggi dimiliki oleh siswa SMA C, yang dalam nilai pretes paling rendah dibandingan SMA lainnya.Kata kunci : model pembelajaran intertekstualitas